The destroyers for true knowledge from the viewpoint of Allama Tabatabai - narges nazarnejad; Zahra Izy (حکمت صدرایی, 2016)
This article tries to explain the viewpoint of Allama Tabatabai, one of the great Muslim  philosophers, concerning true  knowledge and its destroyers. Allama  believes that knowledge about names and attributes  of  God  is  the  true  knowledge  and  is the  origin of happiness and the perfection of human beings. In the epistemological system of Allama Tabatabai, the reality of science is an existential matter and is a grace from the upper world to a human being's heart (soul). A human being – with his capacity and preparation - can unite with Active Intellect to get forms of it. By looking  into Allam's works, one can find that destroyers such as: deviation from the judgment of the intellect,  mere naturalism and rationalism, ignorance of inward  journey, lack of moderation of soul's faculties, and demon's intervention, are some examples of cognitive and non-cognitive destroyers for knowledge  that  result in not receiving necessary capabilities for getting true knowledge.